Answer:
a) 1/27
b) 16
c) 1/8
Explanation:
a)
![x^(-3/2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/7p8iksklf4e44432kkldrp4zghl17mipjb.png)
One of the properties of the exponents tells us that when we have a negative exponent we can express it in terms of its positive exponent by turning it into the denominator (and changing its sign), so we would have:
![x^(-3/2)=(1)/(x^(3/2) )](https://img.qammunity.org/2020/formulas/mathematics/high-school/170gnsas62hlv6rgcv3jex3c7bhm1b29w4.png)
And now, solving for x = 9 we have:
![(1)/(x^(3/2))=(1)/(9^(3/2) ) =(1)/(27)](https://img.qammunity.org/2020/formulas/mathematics/high-school/o21yyzlsp62d0azc4766asjdj6qwbce0l4.png)
b)
![y^(4/3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/txasq69s222vqpthzs6l1ls8er8suzoaql.png)
This is already a positive rational exponent so we are just going to substitute the value of y = 8 into the expression
![y^(4/3)=8^(4/3)=16](https://img.qammunity.org/2020/formulas/mathematics/high-school/v5ooy4axc9e49dyvdc257hkmu56rqaor6t.png)
c)
![z^(-3/4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/pkea10puitevhggi8q66orm5v0jy277g8p.png)
Using the same property we used in a) we have:
![z^(-3/4)=(1)/(z^(3/4) )](https://img.qammunity.org/2020/formulas/mathematics/high-school/g3equg7fc3eipd8zq35q8z8cx5ljygrrpt.png)
And now, solving for z = 16 we have:
![(1)/(z^3/4) } =(1)/(16^(3/4) ) =(1)/(8)](https://img.qammunity.org/2020/formulas/mathematics/high-school/hgv57o65wz71z4ej6qi915oshh44234g01.png)